January Effect di Indonesia Periode 2017 – 2019 - Ratrini, Gusti Ayu; Suartana, I Wayan (E-Jurnal Akuntansi, 2021)
The January Effect is one of the seasonal anomalies, which reveals that stock returns in January tend to be higher than in months other than January. This study aimed to examine and analyze the existence of the January effect using abnormal return and trading volume activity (TVA) variables. The presence of the January Effect was researched on companies listed on the Indonesia Stock Exchange (IDX) and continues to be included in the Investor33 Index during 2017-2019. The samples studied were 25 companies. It was selected using purposive sampling method. The results of the normality test showed that the data was not normally distributed. Thus, only the non-parametric test, namely the Wilcoxon Signed Rank Test, can be used as a data analysis technique. Based on the analysis conducted, it was found that there was a significant difference in abnormal returns and no significant difference in TVA in January and other than January. Therefore, it can be concluded that statistically, the January Effect occurred in Indonesia during the test period indicated by abnormal returns. Keywords: January Effect; Abnormal Return; TVA.